Pelatihan Perencanaan Penggunaan Uang Keluarga Bagi Ibu PKK Desa Cot Muda Itam Kecamatan Peureulak - Ismuhadi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Family financial management is a crucial aspect in shaping the prosperity and sustainability of life for every family. To improve understanding and planning skills for using family money, this training was specifically designed for PKK (Family Welfare Empowerment) mothers in Cot Muda Itam Village, Peureulak District. This training aims to provide deeper knowledge about financial management and help PKK mothers to plan wise use of family money. Cot Muda Itam Village is part of Peureulak District, which is known for its unique characteristics and potential resources. However, there are still economic challenges faced by most families in this village. Therefore, efforts are needed to increase public understanding, especially PKK mothers, in managing family finances in order to achieve better prosperity